Respuesta :

Answer:

The answer is B

Step-by-step explanation:

Since -2/3 multiplied by 3 equals -2, all you need to do is -2+1 which equals -1 which is the same number y is supposed to be.  

Hope this helps

Answer:

The answer is B.

Step-by-step explanation:

You have to substitute x values into the equation to see if it matches y values in the table :

[tex]y = - \frac{2}{3}x + 1[/tex]

[tex]sub \: \: x = 3[/tex]

[tex]y = - \frac{2}{3} (3) + 1 = - 1[/tex]

[tex]sub \: \: x = 6[/tex]

[tex]y = - \frac{2}{3} (6) + 1 = - 3[/tex]

[tex]sub \: \: x = 9[/tex]

[tex]y = - \frac{2}{3} (9) + 1 = - 5[/tex]